1988
DOI: 10.1007/bf00172628
|View full text |Cite
|
Sign up to set email alerts
|

Trazodone in late life depressive states: a double-blind multicenter study versus amitriptyline and mianserin

Abstract: Seventy five elderly depressed in-patients, ages ranging from 60 to 83 years, diagnosed as Major Depression according to DSM III were treated, under double-blind conditions, with 75 mg Amitriptyline (AMI) (26 patients), 60 mg Mianserin (MIA) (24 patients) or 150 mg Trazodone (TRZ) (25 patients) p.o. for 5 weeks. There were no differences in the clinical outcome between the three groups of patients at the end of the trial, with a significant amelioration (P < 0.01) at the Hamilton Rating Scale for Depression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 12 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Georgotas et al 187 * Feighner et al 34 Altamura et al 183 Georgotas et al 207 * Gerner al. 38 Altamura et al 20 Georgotas et al 208 * Gwirtsman et al 41 Altamura et al 21 Georgotas et al 209 * Hutchinson et al 42 Ather et al 22 Gerner et al 38 Merideth et al 50 184 Jarvik et al 44 Scardigli & Jans 194 * Chesrow et al 185 * Katz et al 46 Siegfried & O'Connolly 56 Cohn et al 26 Kernohan et al 189 * Wakelin 60 Cohn et al 25 Koncevoj et al 211 21 Lakshmanan et al 49 Falk et al 33 Cohn et al 25 Feighner & Cohn 35 Lazarus et al 213 * De Vanna et al 28 Georgotas et al 36 Merideth et al 50 39 Feighner et al 34 Guillibert et al 40 Reynolds et al 215 44 Hutchinson et al 42 Katz et al 46 Schneider et al 219 54 Waite et al 59 Merideth et al 50 Phanjoo et al 181 40 Georgotas et al 36 Hutchinson et al 229 …”
Section: Klawansky 83 (M)mentioning
confidence: 99%
See 1 more Smart Citation
“…Georgotas et al 187 * Feighner et al 34 Altamura et al 183 Georgotas et al 207 * Gerner al. 38 Altamura et al 20 Georgotas et al 208 * Gwirtsman et al 41 Altamura et al 21 Georgotas et al 209 * Hutchinson et al 42 Ather et al 22 Gerner et al 38 Merideth et al 50 184 Jarvik et al 44 Scardigli & Jans 194 * Chesrow et al 185 * Katz et al 46 Siegfried & O'Connolly 56 Cohn et al 26 Kernohan et al 189 * Wakelin 60 Cohn et al 25 Koncevoj et al 211 21 Lakshmanan et al 49 Falk et al 33 Cohn et al 25 Feighner & Cohn 35 Lazarus et al 213 * De Vanna et al 28 Georgotas et al 36 Merideth et al 50 39 Feighner et al 34 Guillibert et al 40 Reynolds et al 215 44 Hutchinson et al 42 Katz et al 46 Schneider et al 219 54 Waite et al 59 Merideth et al 50 Phanjoo et al 181 40 Georgotas et al 36 Hutchinson et al 229 …”
Section: Klawansky 83 (M)mentioning
confidence: 99%
“…Gerner et al 38 Phanjoo et al 181 * Jarvik et al 44 Altamura et al 183 Schone & Ludwig 55 Altamura et al 20 Kane et al 45 Altamura et al 21 Katz et al 46 …”
Section: Salzman 78 (R)mentioning
confidence: 99%
“…As observed in clinical trials, peripheral anticholinergic effects are less frequent than with tricyclics. Of note, the lack of cardiovascular side effects such as increased heart rate and hypotension is a further important advantage of Mianserin [95,96]. Mianserin is indicated for the treatment of depression associated with anxiety and agitation and, like Mirtazapine, it is particularly indicated for patients experimenting insomnia [97].…”
Section: Noradrenergic and Specific Serotonergic Antidepressantsmentioning
confidence: 99%
“…One study including alprazolam (Beutler et al, 1987), another study including alprazolam and imipramine (Weissman et al, 1992) and a third study including sulpiride and placebo (Kivela and Lehtomaki, 1987) were excluded because patients received psychotherapy in addition to antidepressant treatment. We assumed the two Italian multicentre trials (Altamura et al, 1988(Altamura et al, , 1989a were separate studies. We treated Dunner et d ' s (1992) paper as one study because only the combined data were reported, even though the title indicates it was based on two studies.…”
Section: General Findingsmentioning
confidence: 99%